Identification of macronutrients deficiencies in three lowland soils from Minas Gerais, Brazil - Abreu, Cleide Aparecida de; Lopes, Alfredo Scheid (Pesquisa Agropecuaria Brasileira, 2014)
This work was developed, using the missing element technique under greenhouse conditions, aiming to evaluate: a) the deficiencies of macronutrients in three lowland soils, as well as the relative importance of these deficiencies; b) the reduction of natural soil fertility in relation to macronutrients through four successive croppings. Corn was used as test plant and the following parameters were evaluated: dry matter production of aerial part, total absorption of macronutrients for the 1st and 4th cropping, and soil macronutrient analyses after 1st and 4th cropping. Considering the accumulative dry matter of aerial part for the four consecutive croppings, a significant decrease was observed by absence of K, N and P in the Humic Gley soil material from Careaçu: S, P and N in the Humic Gley soil material from Uberaba, and S, N, K in the Organic soil. For the 1st cropping, a depressive effect was observed on dry matter of aerial part by absence of P, K and Ca in the Humic Gley from Careaçu; of P and S in the Humic Gley from Ubereba, and of P in the Organic soil. New deficiencies were observed in all soil materials with successive cropping. It was concluded that: a) there is a generalized and immediate P deficiency and Ca, S and K deficiencies in some situations. This justifies the necessity of criterious quantitative evaluations of availability of macronutrients in these soils; b) the decline in dry matter production with successive cropping, except in absence of Ca and Mg, indicates the impossibility of maintainance of high productivity in these soils without an equilibrated continuous fertilization.